2020
DOI: 10.2337/dc20-0822
|View full text |Cite
|
Sign up to set email alerts
|

Childhood BMI and Fasting Glucose and Insulin Predict Adult Type 2 Diabetes: The International Childhood Cardiovascular Cohort (i3C) Consortium

Abstract: Objective: To examine childhood body mass index (BMI), fasting glucose and insulin in relation to incident adult type-2 diabetes mellitus (T2DM). Research Design and Methods: We used data from The International Childhood Cardiovascular Cohort Consortium. Data included childhood measurements (age 3-19) obtained during the 1970s-90s, a health questionnaire including self-report of adult T2DM (occurrence age, medication use) obtained at mean age 40 years, and a medical diagnosis registry (Finland). Results: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
(27 reference statements)
2
20
3
Order By: Relevance
“…More research with a larger sample size is necessary in order to identify clinical predictors for the development of type 2 diabetes during puberty, as it is still a relatively rare disorder. However, findings from the current study and others [ 37 39 ] suggest that failure to see improvements in insulin sensitivity in late puberty portends a higher risk of persistent insulin resistance.…”
Section: Discussioncontrasting
confidence: 66%
“…More research with a larger sample size is necessary in order to identify clinical predictors for the development of type 2 diabetes during puberty, as it is still a relatively rare disorder. However, findings from the current study and others [ 37 39 ] suggest that failure to see improvements in insulin sensitivity in late puberty portends a higher risk of persistent insulin resistance.…”
Section: Discussioncontrasting
confidence: 66%
“…The i3C study also hinted at this from a single childhood timepoint and the Early Bird study showed that glucose concentrations track through early childhood into adolescence. 24,28 These results should convince paediatricians to measure glucose concentrations in children, and policy makers to promote preventive measures at a younger age. Measurement of birth length and head circumference in addition to the usual measurement of weight would add to prediction of risk of future diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…There are few lifecourse studies like ours. 24 Impaired β-cell secretion from an early age was found in both glucose intolerant men and women; men also had diminished insulin sensitivity and thus a ‘double defect’. At 18 years, they had both lower insulin secretion and sensitivity, the latter suggesting either an effect of adolescence and/or glucotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[13] These women had higher glucose and lower disposition index from childhood and early adolescence (6, 12 years of age) [18] Similarly, diabetes at 40 years of age was predicted by higher childhood glucose in the cohorts in the i3C study. [19] A retrospective search of records of women diagnosed with 'GDM' in the Kaiser Permanente clinic showed higher glucose and lipid abnormalities years before pregnancy.…”
Section: Discussionmentioning
confidence: 99%